A novel and simple treatment for control of sulfide induced sewer concrete corrosion using free nitrous acid. (1st March 2015) - Sun, Xiaoyan; Jiang, Guangming; Bond, Philip L.; Keller, Jurg; Yuan, Zhiguo
Abstract: Improved technologies are currently required for mitigating microbially induced concrete corrosion caused by the oxidation of sulfide to sulfuric acid in sewer systems. This study presents a novel strategy for reducing H2 S oxidation on concrete surfaces that accommodate an active corrosion biofilm. The strategy aims to reduce biological oxidation of sulfide through treating the corrosion biofilm with free nitrous acid (FNA, i.e. HNO2 ). Two concrete coupons with active corrosion activity and surface pH of 3.8 ± 0.3 and 2.7 ± 0.2 were sprayed with nitrite. For both coupons, the H2 S uptake rates were reduced by 84%–92% 15 days after the nitrite spray. No obvious recovery of the H2 S uptake rate was observed during the entire experimental period (up to 12 months after the spray), indicating the long-term effectiveness of the FNA treatment in controlling the activity of the corrosion-causing biofilms. Live/Dead staining tests on the microorganisms on the concrete coupon surfaces demonstrated that viable bacterial cells decreased by > 80% 39 h after the nitrite spray, suggesting that biofilm cells were killed by the treatment. Examination of a corrosion layer within a suspended solution, containing the corrosion-causing biofilms, indicated that biological activity (ATP level and ratio of viable bacterial cells) was severely decreased by the treatment, confirming the bactericidal effect of FNA on the microorganisms in the biofilms. While field trials are still required to verify its effectiveness, it has been demonstrated here that the FNA spray is potentially a very cheap and effective strategy to reduce sewer corrosion. Graphical abstract: Highlights: FNA effectively deactivates SOB in the sewer corrosion layer. SUR substantially decreases after FNA treatment. There is little recovery of SUR over one year after FNA treatment. FNA treatment is potentially a cheap and effective technology to control corrosion.